Kontekstualisasi Hukum Islam: Telaah atas Pemikiran Hukum KH. MA Sahal Mahfudz - Miftahul Huda (Justicia Islamica, 2006)
This study aims to analyze the Islamic legal thought of KH. MA Sahal Mahfudz in the context of Islamic legal reform relevant to social development. KH. MA Sahal Mahfudz is known for his approach of balancing text (nash) and context in applying Islamic law. This study uses a qualitative method with a literature study approach, examining his works and thoughts, especially related to social fiqh. The results of the study show that KH. MA Sahal Mahfudz's thinking emphasizes the importance of contextualizing Islamic law so that it remains relevant to changing times without losing its shar'i values. Through the maqashid sharia approach and the contextual ijtihad method, he offers a formulation of Islamic law that is more responsive to social realities. His thoughts contribute to the development of dynamic fiqh, especially in social issues and Islamic legal policy in Indonesia.